Landscape context explains changes in the functional diversity of regenerating forests better than climate or species richness. Issue 10 (October 2017) - Sams, M. A.; Lai, H. R.; Bonser, S. P.; Vesk, P. A.; Kooyman, R. M.; Metcalfe, D. J.; Morgan, J. W.; Mayfield, M. M.
Abstract: Aim: A rich literature on forest succession provides general expectations for the steps forests go through while reassembling after disturbance, yet we still have a surprisingly poor understanding of why the outcomes of forest recovery after logging (or other disturbances) vary so extensively. In this paper, we test the hypothesis that regional species pool, system productivity, climate and landscape structure are important drivers of forest reassembly outcomes. Location: Transect 1, 500 km in length along the east coast of Australia. Time period: Survey of 50‐ to 60‐year‐old rain forest regrowth and primary forest conducted in 2012 and 2013. Major taxa studied: Rain forest plants. Methods: In this study, we compare species and functional diversity patterns in pairs of remnant and regrowth ('secondary') rain forests spread across a 1, 500 km climate and productivity gradient along the east coast of Australia. Our controlled natural experiment was designed to test the importance of regional species pool, system productivity, climate and landscape structure as drivers of species and functional diversity in regenerating forests. Notably, our study design allowed us to hold soil type, general forest type and disturbance history relatively constant in order to test our hypotheses effectively. Results: Counter to expectations, few tested factors were strongly related to the recovery of species or functional diversity in regenerating Australian rain forests. The extent of local forest fragmentation was the only factor strongly related to differences between regrowth forests and primary forest remnants, and then only for functional diversity. We found no evidence that species diversity is a reasonable proxy for, or potential driver of, functional diversity patterns. Main conclusions: Our findings suggest that forest functional recovery over decades is influenced more by regional landscape context than distinct assembly processes operating across climate and productivity gradients.